'What is in a Name?': The Role of (Different) Identities in the Multiple Proxy Wars in Syria. (4th May 2018) - Phillips, Christopher; Valbjørn, Morten
Abstract: Post-uprisings Middle East politics is frequently described as a 'regional cold war' involving proxy warfare that emphasises the role of shared identities linking external and local actors. But does the 'content' of identities impact proxy war dynamics? This article considers the present 'battle for Syria', a local conflict that became a theatre for multiple proxy wars involving actors emphasising identities on various levels, most notably national, religious/ sect and ethnic. It suggests that identity content does matter, with global powers more reluctant than regional players to back groups identifying at sub-national level, while foreign non-state actors are enthusiastic backers of sub-national identity.